(untitled) (Scientific journal of the Fergana State University, 2023)
Length-weight relations (LWR) were estimated for 7 indigenous and invasive fish species from the ditches of Qoʻshtepa District, Fergana Region: Abbottina rivularis, Alburnus sp., Gobio lepidolaemus, Petroleuciscus squaliusculus, Pseudorasbora parva, Rhodeus ocellatus, Triplophysa strauchii. Measurements were taken for total length (0.1 cm precision) and total weight (0.1 g precision). The LWR parameters were determined using a linear logarithmic regression model of weight against length in which values for the slope of the regression, b, that are higher and lower than 3 indicate positive and negative allometric growth, respectively. The estimated values of parameter b ranged from 3.012 (Triplophysa strauchii) to 3.260 (Rhodeus ocellatus). The correlation coefficient (r2) values varied from 0.980 to 0.998, indicating a strong positive relation between length and weight.